OPTIMIZING EMPLOYEE PERFORMANCE: THE IMPACT OF TRAINING AND DEVELOPMENT, WORK-LIFE BALANCE, AND WORKPLACE HAPPINESS - Rini Juni Astuti; Fika Amanda Febrianti (Adisam Publisher, 2024)
Human resources are important and primary in every company because if the company experiences an increase, it is based on competent human resources. Strategic human resource management (HRM) must allow adaptation of HRM practices, namely knowledge and behavior in employees based on organizational needs. In this study, there is a phenomenon in which employees work suboptimally and feel unable to complete their performance, which results in decreased performance. In addition, the results of inconsistencies in previous studies examined employee performance. Thus, this study contributes to analyzing the influence of training and development, work-life balance, and happiness at work on employee performance. Multiple linear regression analysis was used to test the proposed hypothesis. The number of data used was 130 employees in peanut manufacturing in Pati, Central Java, Indonesia. The findings show that employee performance is affected by training and development, work-life balance, and happiness at work. Employees feel that these programs help improve their performance and increase their satisfaction, pride, and motivation to work more effectively. Therefore, organizations must continue to strengthen these programs to improve employee performance.